2020
DOI: 10.32615/ps.2020.010
|View full text |Cite
|
Sign up to set email alerts
|

Leaf gas exchange, oxidative stress, and physiological attributes of rapeseed (Brassica napus L.) grown under different light-emitting diodes

Abstract: Through its impact on morphogenesis, light is the key environmental factor that alters plant structural development; however, the understanding how light controls plant growth and developmental processes is still poor and needs further research. For this purpose, a Petri dish and pot experiment was conducted to investigate the effects of different LEDs, i.e., white light (WL), red light (RL), blue light (BL), and orange light (OL) on morphology, gas-exchange parameters, and antioxidant capacity of Brassica nap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 80 publications
0
25
1
Order By: Relevance
“…Cu in excess also involves in the generation of large amount of reactive oxygen species (ROS) because of depletion of low molecular antioxidants and distribution of metabolic pathways that shows oxidative stress in plants [5,13,21,[87][88][89]. ROS production in the leaves is scavenging by antioxidants such as SOD and POD [16,17,[90][91][92][93]. In this analysis, high concentration of Cu in the nutrient solution causes high MDA content, proline, and increased enzymes with antioxidant activities such as SOD and POD in C. capsularis roots and leaves (Figure 2, Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Cu in excess also involves in the generation of large amount of reactive oxygen species (ROS) because of depletion of low molecular antioxidants and distribution of metabolic pathways that shows oxidative stress in plants [5,13,21,[87][88][89]. ROS production in the leaves is scavenging by antioxidants such as SOD and POD [16,17,[90][91][92][93]. In this analysis, high concentration of Cu in the nutrient solution causes high MDA content, proline, and increased enzymes with antioxidant activities such as SOD and POD in C. capsularis roots and leaves (Figure 2, Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Water deficit conditions are believed to reduce turgidity, impair nutrition balance, gas exchange and stomatal regulation [14,[56][57][58], thereby reducing the growth and yield of plants. In our study, water deficiency reduced the A, A/E and g s .…”
Section: Discussionmentioning
confidence: 99%
“…B. napus is resistant to heavy metal stress but showed much higher production of O −2 , MDA, and H 2 O 2 when grown in metal-polluted soil [ 16 , 18 ]. However, several studies also suggested that B. napus has a very strong defense system (antioxidants), which ultimately increased their activities to protect the plant against the metal stress environment [ 2 , 13 , 14 ]. In the current study, Cr toxicity caused oxidative stress in the B. napus by increasing malondialdehyde (MDA) content in the roots and leaves of the plants ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Oil rape ( Brassica napus L.) is the world’s second most important source of vegetable oil and has the capacity to accumulate in the edible portion of toxic heavy metals from heavy-metals soil polluted by irrigation of wastewater [ 2 , 13 ]. B. napus is cultivated extensively around the worldwide and the stress relief of heavy metals has also been widely investigated in different environmental conditions [ 2 , 14 ].…”
Section: Introductionmentioning
confidence: 99%